PEMEROLEHAN SINTAKSIS ANAK USIA 5 TAHUN DI KENAGARIAN KOTO BARU KECAMATAN KUBUNG KABUPATEN SOLOK (KAJIAN PSIKOLINGUISTIK) - Fitri Ramadhani; Zona Rida Rahayu; Elan Halid (JELISA (Jurnal Edukasi dan Literasi Bahasa), 2022)
The background of this research is to explore and examine more deeply related to syntax acquisition in children aged 5 years by focusing attention on the development of syntax acquisition and sentence structure when children are at their pride. This study aims to describe the acquisition of syntax for 5 year old children in Kenagarian Koto Baru, Kubung District, Solok Regency (Psycholinguistic Study). This type of research is qualitative using descriptive method. The research subject was a girl named Hidayatul Hafidzah (HH) when she was 5 years old. The data for this study were obtained from data sources in the form of conversational texts produced by preschool-aged children. Data collection techniques were carried out using interviews, observation, documentation and audiovisual techniques which contained utterances in each speech event. The data analysis technique used in this study is in the form of sentences conveyed by children based on their functions in HH's daily speech. The steps taken by researchers in managing data are reducing data, identifying data, classifying data, analyzing data, and concluding the data obtained. Data were analyzed based on the forms and functions that exist in the language of children aged 5 years. Based on research findings obtained in the field found 65 data. Language elements included in the scope of syntax are (a) phrases, (b) clauses divided into two parts, namely independent clauses and dependent clauses and (c) sentences divided into three parts, namely declarative sentences, imperative sentences, and interrogative sentences. So, the most frequently found syntax acquisition sentences. This is because it is evident from the utterances found by Hidayatul Hafidzah (HH) that are realized in the form of multiwords.